1999
DOI: 10.1021/es990145+
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Accelerated Solvent Extraction (ASE) for Analysis of Pesticide Residues in Soil

Abstract: Accelerated solvent extraction, or ASE, is a new extraction technique that is similar in principle to Soxhlet extraction, but the use of elevated temperature and pressure with ASE allows the extraction to be completed within a short time and with a small quantity of solvent. In this study, we investigated the effect of residue aging, solvent type, and ASE conditions on the recovery of atrazine and alachlor from different soils and compared the efficiency of ASE with that of Soxhlet and solvent−shake extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(41 citation statements)
references
References 19 publications
2
37
0
2
Order By: Relevance
“…An Accelerated Solvent Extraction (ASE) device (ASE 200, Dionex) was used to extract the soils. The ASE-extraction was similar to the extraction method previously described by Gan et al (Gan et al, 1999). In this study, a methanol-water solution (4:1 v:v) was used for extraction since results showed slightly higher residual 14 C-activity in the extracts than when using methanol alone, consistent with previous findings (Huang and Pignatello, 1990).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…An Accelerated Solvent Extraction (ASE) device (ASE 200, Dionex) was used to extract the soils. The ASE-extraction was similar to the extraction method previously described by Gan et al (Gan et al, 1999). In this study, a methanol-water solution (4:1 v:v) was used for extraction since results showed slightly higher residual 14 C-activity in the extracts than when using methanol alone, consistent with previous findings (Huang and Pignatello, 1990).…”
Section: Discussionsupporting
confidence: 86%
“…As given in Figure 1, most residual 14 C-activity was extracted in the first extraction step. The applied ASE-settings in accordance with Gan et al (Gan et al, 1999) were highly effective for the extraction of aged atrazine residues from soil and homogenized gravel using a methanol-water solution, as previously suggested (Huang and Pignatello, 1990). In comparison to previous extraction studies using vigorous shaking with water (Jablonowski et al, 2008a) or Soxhlet extraction (data not shown), the ASE yielded a considerably greater amount of aged atrazine residues; approximately 60 % of the total residues in the respective layer in the case of soil and 93 % in the case of homogenized gravel (Table 1).…”
Section: Resultsmentioning
confidence: 74%
“…But as for PCB66, PCB118, PCB153, PCB138, PCB180 and PCB170, it was contrary. This different trend was attributed to the different polarities of these congeners and solvents [38]. Furthermore, isopropanol showed its superiority over hexane/acetone and methanol in all cases.…”
Section: Optimization Of the Solvothermal Proceduresmentioning
confidence: 91%
“…Although PCBs are insoluble under ambient atmosphere and temperature, bound PCBs were quickly dissolved by organic solvent in the sealed pressure vessel at the increased temperature. The role of pressure was important in that a slight higher pressure keeps the solvent in the liquid phase at a high temperature as described by Gan et al [38] for accelerated solvent extraction. According to previous reports [12,13], bound PCBs were partitioned into different components of soil.…”
Section: Solvothermal Extraction Mechanismsmentioning
confidence: 99%
“…It can also be assumed that with such a difficult matrix, rich in fats, carbohydrates and proteins, at least one of the following processes should be used: microwave mineralization, increased pressure, incineration, and dissolution in acid. Taking these four methods into account, four basic groups of methods of preparing vegetable oil samples can be distinguished in the determination of heavy metals [7,[10][11][12][13][14][15]:…”
mentioning
confidence: 99%